Upaya Peningkatan Pengetahuan Ibu Hamil Melalui Edukasi Tanda Bahaya Kehamilan di Pustu (Puskesmas Pembantu) Sungai Beras Hilir - Saddam Muhdi; Tega Maulana Fitrah; Intan Irwani; Rizky Rahmi Darwita; Tiara Suryantika; Nuripa Kasani; Faisal Iqbal; Ikha Hafni Putri; Nurlisa Gustina Putri; Nengreha Paujiah; Aditha Pratama; Mutya Aryanti; Mutia Rahma; Bilda Prinanti Sinaga; Siti Laig; Agnes Videlia; Dwi Mardiana; Risa Andella (Lembaga Pengembangan Kinerja Dosen, 2024)
The importance of special attention to mothers and children in health services is reflected in the high maternal mortality rate (MMR), which shows the quality of health services in a region. Pregnant women's knowledge of the danger signs of pregnancy is a key factor in preventing complications and death. Maternal and Child Health (KIA) books and pregnancy class programs are one of the efforts to increase this knowledge. This research aims to increase pregnant women's understanding of the danger signs of pregnancy through counseling in Sungai Beras Hilir Village. The methods used were counseling using KIA books, discussions and demonstrations by the Kulim Jaya Community Health Center team and KKN students. The results show an increase in pregnant women's knowledge about the danger signs of pregnancy and prevention of preeclampsia after being given counseling. In conclusion, this activity is effective in increasing pregnant women's understanding of the importance of knowing the danger signs of pregnancy and preventing them, as well as motivating them to carry out routine health control.